Studies on Energetic Salts Based on (2, 4, 6‐Trinitrophenyl)guanidine. Issue 2 (17th February 2016) - Klapötke, Thomas M.; Mieskes, Frank; Stierstorfer, Jörg; Weyrauther, Michael
Abstract: (2, 4, 6‐Trinitrophenyl)guanidine was synthesized and its thermal and energetic properties were investigated. The reaction of (2, 4, 6‐trinitrophenyl)guanidine with different acids, such as nitric, picric, perchloric, and hydrochloric acid results in protonation of (2, 4, 6‐trinitrophenyl)guanidine and the formation of the corresponding salts (cation : anion ratio 1 : 1). The reactions are performed at ambient temperature in H2 O or EtOH and produce qualitatively pure products with energetic properties, which are typical of those of secondary explosives. The compounds were characterized using multinuclear NMR spectroscopy, IR and Raman spectroscopy, as well as mass spectrometry. Single crystal X‐ray diffraction studies were performed and the structures of the four different salts at low temperatures were determined. The thermal stabilities were measured using differential scanning calorimetry (DSC). The sensitivities were determined using the BAM drophammer and friction tests. The heats of formation were calculated by the atomization method based on CBS‐4M enthalpies. Using these values as well as the X‐ray or pycnometric densities, several detonation parameters such as the detonation pressure, velocity, energy, and temperature were computed using the EXPLO5 code. Abstract :